2018
DOI: 10.1080/21645515.2018.1430539
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective and prospective look at strategies to increase adolescent HPV vaccine uptake in the United States

Abstract: The HPV vaccine debuted more than ten years ago in the United States and many strategies have been evaluated to increase HPV vaccination rates, which include not only improving current vaccination behaviors but also sustaining these behaviors. Researchers and practitioners from a variety of backgrounds have engaged in this work, which has included efforts directed at public health and government policies, health education and health promotion programs, and clinical and patient-provider approaches, as well as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 92 publications
4
15
0
Order By: Relevance
“…Both Trusters (HPV) and the Ambivalent (COVID19) are ripe for receiving inoculation messages against misinformation across vaccine safety, effectiveness, the testing process, transparency, ingredients, and adverse reactions. Similar misinformation domains have been recognized in the literature across HPV and COVID-19 yet never in this social media vaccine frame-stance context at this scale (Calo et al, 2021;Head et al, 2018;Jamison et al, 2020;Kim et al, 2020;Loomba et al, 2021;Massey et al, 2020;Sundstrom et al, 2021;Van der Linden et al, 2016;Zimet et al, 2013).…”
Section: Vaccine Hesitancy Profiles As Person Centered Audience Segmentation For Targeted Campaignssupporting
confidence: 65%
“…Both Trusters (HPV) and the Ambivalent (COVID19) are ripe for receiving inoculation messages against misinformation across vaccine safety, effectiveness, the testing process, transparency, ingredients, and adverse reactions. Similar misinformation domains have been recognized in the literature across HPV and COVID-19 yet never in this social media vaccine frame-stance context at this scale (Calo et al, 2021;Head et al, 2018;Jamison et al, 2020;Kim et al, 2020;Loomba et al, 2021;Massey et al, 2020;Sundstrom et al, 2021;Van der Linden et al, 2016;Zimet et al, 2013).…”
Section: Vaccine Hesitancy Profiles As Person Centered Audience Segmentation For Targeted Campaignssupporting
confidence: 65%
“…5 In data from the 2016 National Immunization Survey, only 65% of adolescent females and 56% of males initiated the two- or three-dose vaccine series with 50% of adolescent females and 38% of males completing the series. 6 Not only are these rates lower than the Healthy People 2020 goal of 80% vaccination, but there is also a distinct difference in the number of adolescent males being vaccinated compared with females. 7,8 This disparity may not only be due, in part, to the 5-year lag in the Centers for Disease Control and Prevention (CDC)'s recommendation for the HPV vaccine in adolescent males (2011) compared with adolescent females (2006), but it may also be attributed to the “feminization of HPV” as a women's problem emphasizing the need for frequent and early recommendations by health care providers to parents of adolescent males in particular.…”
Section: Introductionmentioning
confidence: 99%
“…The modification of factors that negatively affect parental vaccination decision-making is a key strategy to improving HPV vaccination rates [ 15 , 16 ]. A 2019 systematic review of 41 US-based studies exploring HPV vaccine beliefs found four negative beliefs—perceived adverse effects (ie, promotes sexual activity, too new, and causes illness), perceived lack of necessity (not sexually active), morality concerns (stigmatizing recipients), and skepticism about effectiveness—and one positive belief, that it prevents STIs, across the literature [ 17 ].…”
Section: Introductionmentioning
confidence: 99%